Synergistic fibrinolysis: The combined effects of tissue plasminogen activator and recombinant staphylokinase in vitro - Aisina, Roza; Mukhametova, Liliya; Varfolomeyev, Sergei (Biochimica et biophysica acta, 2016)
Mechanisms of fibrin-specificity of tissue plasminogen activator (tPA) and recombinant staphylokinase (STA) are different, therefore we studied in vitro the possibility of the synergy of their combined thrombolytic action. Thrombolytic effects of tPA, STA and their combinations were measured by lysis rate of human plasma clot and side effects were evaluated by decreasing in fibrinogen, plasminogen and α2-antiplasmin levels in the surrounding plasma at 37°C in vitro. STA and tPA induced dose- and time-dependent clot lysis: 50% lysis in 2h was obtained with 30nM tPA and 75nM STA, respectively. At these concentrations, tPA produced greater degradation of plasma fibrinogen than STA. According to a mathematical analysis of dose–response curves by the isobole method, combinations of tPA and STA caused a considerable synergistic thrombolytic effect. The simultaneous and sequential combinations of tPA (<4nM) and STA (<35nM) induced a significant fibrin-specific synergistic thrombolysis, which was more pronounced in 2h at simultaneous combinations than at sequential addition of STA after 30min of tPA action. Simultaneous combination of 2.5nM tPA and 15nM STA showed a maximal 3-fold increase in thrombolytic effect compared to the expected total effect of the individual agents. Sequential combinations caused a lower depletion of plasma proteins compared to simultaneous combinations. The simultaneous and sequential combinations of tPA and STA possessed synergistic fibrin-specific thrombolytic action on clot lysis in vitro. The results show that combined thrombolysis may be more effective and safer than thrombolysis with each activator alone. •Combinations of tPA and recombinant STA possess synergistic thrombolytic action on clot lysis in vitro.•Synergistic combinations of tPA and STA induce the lower fibrinogenolysis than the expected effect of the individual agents.•TPA functions as the trigger of fibrinolysis which is continued by STA.